Lung Ultrasound Findings in the Postanesthesia Care Unit Are Associated With Outcome After Major Surgery: A Prospective Observational Study in a High-Risk Cohort. (January 2021) - Zieleskiewicz, Laurent; Papinko, Mickael; Lopez, Alexandre; Baldovini, Alice; Fiocchi, David; Meresse, Zoe; Boussuges, Alain; Thomas, Pascal Alexandre; Berdah, Stephane; Creagh-Brown, Ben; Bouhemad, Belaid; Futier, Emmanuel; et al.
Abstract : Background: Postoperative pulmonary complications are associated with increased morbidity. Identifying patients at higher risk for such complications may allow preemptive treatment. METHODS: Patients with an American Society of Anesthesiologists (ASA) score >1 and who were scheduled for major surgery of >2 hours were enrolled in a single-center prospective study. After extubation, lung ultrasound was performed after a median time of 60 minutes by 2 certified anesthesiologists in the postanesthesia care unit after a standardized tracheal extubation. Postoperative pulmonary complications occurring within 8 postoperative days were recorded. The association between lung ultrasound findings and postoperative pulmonary complications was analyzed using logistic regression models. RESULTS: Among the 327 patients included, 69 (19%) developed postoperative pulmonary complications. The lung ultrasound score was higher in the patients who developed postoperative pulmonary complications (12 [7–18] vs 8 [4–12]; P < .001). The odds ratio for pulmonary complications in patients who had a pleural effusion detected by lung ultrasound was 3.7 (95% confidence interval, 1.2–11.7). The hospital death rate was also higher in patients with pleural effusions (22% vs 1.3%; P < .001). Patients with pulmonary consolidations on lung ultrasound had a higher risk of postoperative mechanical ventilation (17% vs 5.1%; P = .001). In all patients, the area under the curve for predicting postoperative pulmonary complications was 0.64 (95% confidence interval, 0.57–0.71). CONCLUSIONS: When lung ultrasound is performed precociously <2 hours after extubation, detection of immediate postoperative alveolar consolidation and pleural effusion by lung ultrasound is associated with postoperative pulmonary complications and morbi-mortality. Further study is needed to determine the effect of ultrasound-guided intervention for patients at high risk of postoperative pulmonary complications.